2003
DOI: 10.1093/toxsci/kfh005
|View full text |Cite
|
Sign up to set email alerts
|

Lung Deposition and Clearance of Inhaled Vanadium Pentoxide in Chronically Exposed F344 Rats and B6C3F1 Mice

Abstract: Female F344 rats and B6C3F1 mice were exposed to vanadium pentoxide (V2O5) at concentrations of 0, 0.5, 1, or 2 mg/m3 (rats) and 0, 1, 2, or 4 mg/m3 (mice) for 6 h/day, 5 days/week (for up to 18 months), by whole-body inhalation. Lung weights and lung burdens of vanadium were determined for exposed animals after 1, 5, and 12 days and after 1, 2, 6, 12, and 18 months of V2O5 exposure. Blood vanadium concentrations were determined at 1, 2, 6, 12, and 18 months for all animals including controls. A model that ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 12 publications
0
13
0
3
Order By: Relevance
“…There may be a pathological pattern within the lung which may be associated with the pattern and/or extent of vanadium deposition. [40] Its cumulative effect in lung tissue possibly contributes to the development lung cancer. Indeed, in lung tissue excised from post-mortem investigations, the mean vanadium concentrations of 1.36 ± 0.08 (sd) (1990s) were higher than 1.04 ± 0.05 in the 1960s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be a pathological pattern within the lung which may be associated with the pattern and/or extent of vanadium deposition. [40] Its cumulative effect in lung tissue possibly contributes to the development lung cancer. Indeed, in lung tissue excised from post-mortem investigations, the mean vanadium concentrations of 1.36 ± 0.08 (sd) (1990s) were higher than 1.04 ± 0.05 in the 1960s.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Vanadium lung exposure studies in rats appear to reach a steady state in low exposure groups of 0.5 mg/m 3 . [10] The retention rate of vanadium in rats aged 18 months was 13-15%. [10]…”
Section: Introductionmentioning
confidence: 99%
“…These kinetic studies were reported to show that the lung burdens of vanadium appeared to reach steady-state with time at the lowest administered concentrations (0.5 mg/m 3 for rats and 1 mg/m 3 for mice), but at higher concentrations the lung burdens in both species declined with time after reaching maximum values at about 6 months for rats and 1–2 months for mice. The tabulated data in Dill et al (2004) also suggest that, if the only determinant for lung tumours was the lung burden of vanadium (µg V/g lung) then one might predict the tumour incidences in female rats exposed to 1 or 2 mg/m 3 to be very similar to the incidences in female mice exposed to the same atmospheric concentrations of vanadium pentoxide 27 . This is because the lung burdens at these concentrations in the two species were very similar throughout the exposure period, with eight measurements taken, beginning on day 1 and ending on day 535.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer datasets on deposition and clearance of particles in the respiratory tract of mice are available than for other species (Dill et al, 2004, Kuehl et al, 2012, Oberdorster and Finkelstein, 1995, Raabe et al, 1988). Menache et al (1995) developed particle-size dependent, inhalability curves for humans and a group of small animals based on measurements of particle deposition in the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%